Pengaruh Lingkungan Kerja Positif terhadap Motivasi dan Kinerja Sumber Daya Manusia di Desa Cicalengka Pagedangan Tangerang - Budi Ismanto; Aldila Rahma Putri; Wahyu Andri Wibowo (Jurnal PKM Manajemen Bisnis, 2026)
A positive work environment is an essential factor in enhancing employee motivation and performance, particularly in public sector organizations that play a key role in community services. This community service activity (PKM) aimed to improve understanding and implementation of positive work environment practices to strengthen the motivation and performance of human resources in Cicalengka Village, Pagedangan, Tangerang. The activity was conducted at the Cicalengka Village Office on August 31, 2025, and involved ten lecturers from Universitas Pamulang as facilitators. A total of fifteen village officials participated in the program. The PKM activities were carried out through a combination of lectures, practical sessions, group discussions, and question-and-answer interactions. This participatory method encouraged active involvement and reflection from participants on their daily work practices. The results of the activity showed an increased awareness among participants about the importance of creating a supportive, communicative, and collaborative work environment. Participants also demonstrated improved motivation and readiness to apply the concepts of a positive work culture in their organizational setting. In conclusion, the PKM activity contributed to strengthening the capacity and mindset of village officials toward a more productive and harmonious work environment, which is expected to improve overall performance and service quality in Cicalengka Village.